Physical development of port city case study: Penang / Mazuin Dollah - Dollah, Mazuin (2015)
The thesis concerns about the physical development of port and surrounding cities. The role of port as well a city revealed that there is synergy between them. The aim of the study is to examine the synergy between port and city, including physical characteristics and institutional elements using Penang Port as a case study. The problems mentioned from previous studies that port city is varied and complex. There are studies on port and its cities regarding their issues on complementary and contradictory aspect about the evolution of port city. Some town planners considered that port and city as a separate and alien activity. An occurrence of conflict imbalance happened in port city relationship as the settlement area is build alongside the port area which the resident and the goods use the same highways. Some traditional port activities clash with many urban activities and faced difficulties on physical development to define the transition zones where the spaces reserved for ports and cities crucial to sustainable development. However, as port having the revolution to the modern industries, some researchers agree to locate the cities away from the port. Other than that the port city issues lies on relationship between port authorities and city authorities. The study employs descriptive analysis to achieve the aim. There are five stages which start with preliminary study followed by review of literature pertaining the topic. The third stage is data collection where the study has done ground survey with observation technique by taking importance note and captured the image in study area. The study was organised to interview several institutions regarding the relation related to physical development. They are Majlis Perbandaran Seberang Perai (MPSP), Department of Town and Country Planning, Pulau Pinang (JPBD PP), Penang Port Commission (PPC) and Penang Port Sdn Bhd (PPSB). The purpose of interviewed is to identify the real situation and get perception how these institutions govern the land and port. Stage four is descriptive analysis part where the study has analysed the current land-use using GIS on-line Mapping. The captured images in study area are used to view and explain the current situation. The finding from the analysis identified that the current port city having an intensive mix land-use development. The land-use development also experienced migration outward from the port area. The findings also identified that there are ‘interaction’ exist between land-use types surrounding port and cities as settlement area, industrial and port location. Other than that, the transportation structure as road widening, existing of BORR, improvement of railway track and additional tolled road to cater the port activities. The transportation improvement is purposely to reduce the traffic congestion and avoid the delays case in delivering goods to the port and vice versa. However, the transport infrastructures such as railway track, highways and increasing the new routes caused the shrinking on land supply and giving the bad impact to local people due to their settlements are very close to the transport infrastructure. In terms of port city governance, the port and the city have different institutions with different respective priority. However, the port and the city interface have their unique characteristics with the relations exist between cities and the port and at the same time giving the synergy between them.